2020
DOI: 10.26464/epp2020037
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional electron conic observations for photoelectrons in the Martian ionosphere

Abstract: An analysis is conducted focusing on the bidirectional electron conics at 19-55 eV on Mars q BECs are more likely observed on the nightside and near strong crustal magnetic anomalies q 19-55 eV BECs are formed due to day-tonight transport along cross-terminator magnetic field lines q

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…First, from Figure 2(c), the photoelectron butterfly PADs are most likely to occur in the darkness at nearly all altitudes for almost all energies, except for 41.2 and 57.5 eV in the region above the altitude of 550 km. The occurrence rate in the eclipse is generally above 1%, and comparable to that reported by Cao et al (2020). These darkness observations are found far away from the source region, indicating that photoelectrons are significantly transported from the dayside to below 300 km at least on the nightside, via long magnetic loops (e.g., Xu et al 2016;Cao et al 2021).…”
Section: Dependence On Solar Zenith Angle Altitude and Energysupporting
confidence: 87%
See 4 more Smart Citations
“…First, from Figure 2(c), the photoelectron butterfly PADs are most likely to occur in the darkness at nearly all altitudes for almost all energies, except for 41.2 and 57.5 eV in the region above the altitude of 550 km. The occurrence rate in the eclipse is generally above 1%, and comparable to that reported by Cao et al (2020). These darkness observations are found far away from the source region, indicating that photoelectrons are significantly transported from the dayside to below 300 km at least on the nightside, via long magnetic loops (e.g., Xu et al 2016;Cao et al 2021).…”
Section: Dependence On Solar Zenith Angle Altitude and Energysupporting
confidence: 87%
“…According to the mechanism presented by Cao et al (2020), the generation of photoelectron butterfly PADs observed on the nightside might be related to the day-to-night transport of photoelectrons along closed cross-terminator magnetic field lines. They proposed that the adiabatic pitch-angle evolution of photoelectrons along converging/diverging magnetic field lines should take responsibility for the formation of the butterfly PADs observed in the nightside Martian ionosphere (more details about the mechanism are presented in Section 3.2).…”
Section: Dependence On Solar Zenith Angle Altitude and Energymentioning
confidence: 99%
See 3 more Smart Citations